Erdafitinib diminishes LPS-mediated neuroinflammatory responses through NLRP3 in wild-type mice - Lee, Hyun-ju; Kim, Se Ha; Jung, Tae-Mi; Kim, Yu-Jin; Gu, Chan-Hu; Jeong, Yoo Joo; Song, Jeong-Heon; Hoe, Hyang-Sook (Frontiers in Pharmacology, 2025)
IntroductionErdafitinib is an FDA-approved inhibitor of fibroblast growth factor receptor (FGFR) that is used clinically to treat metastatic urothelial cancer. FGFR activation is involved in proinflammatory responses, but the potential effects of FGFR inhibitors like erdafitinib on neuroinflammatory responses in the brain have not been fully established.MethodsThe effects of pretreatment with 1 μM or 5 μM erdafitinib on proinflammatory responses induced by 1 μg/mL or 200 ng/mL LPS in vitro were evaluated in BV2 microglial cells. For in vivo experiments, 3-month-old C57BL6/N mice were injected (i.p.) daily for 7 days with vehicle (5% DMSO +40% PEG +5% Tween80 + 50% saline) or 10 mg/kg erdafitinib. On the final day, the mice were injected (i.p.) with 10 mg/kg LPS or PBS after erdafitinib administration and sacrificed after 8 h. The mRNA and protein expression of neuroinflammatory-associated molecules were assessed in cells or mouse brain tissue by real-time PCR, immunofluorescence staining, and/or Western blotting.Results and DiscussionIn BV2 microglial cells, erdafitinib pretreatment significantly reduced the increases in proinflammatory cytokines, NLRP3 inflammasome activation and JNK/PLCγ signaling induced by LPS. In C57BL6/N mice, erdafitinib pretreatment significantly suppressed LPS-stimulated microglial/astroglial activation and proinflammatory cytokine expression. Importantly, erdafitinib pretreatment significantly downregulated LPS-induced NLRP3 inflammasome activation and astroglial neuroinflammation-associated molecules in C57BL6/N mice. Collectively, our experiments demonstrate that erdafitinib pretreatment diminishes LPS-induced neuroinflammation by suppressing NLRP3 inflammasome activation in vitro and in vivo and suggest that erdafitinib is a potential therapeutic agent for neuroinflammation-related diseases.